Peningkatan Hasil Belajar Siswa Pada Pembelajaran Penjumlahan Dan Pengurangan Bilangan Pecahan Menggunakan Model Problem Based Learning - Dhani, Vachry; Ahmad, Syafri (Global Action and Education for Society, 2022)
Improving Learning Outcomes using the Problem Based Learning (PBL) Model in the Lesson of Addition and Subtraction of Fractions in Class V SDN 27 Air Children. This study aims to describe the improvement of student learning outcomes by using the Problem Based Learning in learning addition and subtraction of fractions in class V SDN 27 Anak Air. This research is a classroom action research with qualitative and quantitative approaches. The subjects of this study were the fifth grade students of SDN 27 Anak Air, totaling 27 people. The results of this article indicate that the application of the Problem Based Learning (PBL) model to improve student learning outcomes is as follows: Improved learning outcomes with an average value of 73.22 in the first cycle and increased in the second cycle to 83.70. Thus, the application of the Problem Based Learning (PBL) learning model can improve mathematics learning outcomes in the matter of adding and subtracting fractions in class V at SDN 27 Anak Air.